2021
DOI: 10.1109/access.2021.3132667
|View full text |Cite
|
Sign up to set email alerts
|

Building Blocks for GaN Power Integration

Abstract: GaN technology is on the advance for the use in power ICs thanks to space-saving integrated circuit components and the increasing number of integrated devices. This work experimentally investigates a number of key building blocks for GaN power integration. First, an overview of the active and passives devices of the technology is given with focus on area-efficient layouts for power transistors and limitations of on-chip capacitors and inductors with comparison to other IC technologies. Digital and analog basic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…A. Chvá la et al demonstrated a monolithic NAND cell that is based on InAlN/GaN MIS-HEMTs with a maximum gate voltage of 3 V, and confirming the validity of the proposed models [20]. As an essential building block for digital circuits, implementing dual-gate E-mode NAND (DG-NAND) by p-GaN HEMTs with a smaller area provides an optimization method [21]. However, as a result of the limitations of p-GaN technology with low gate breakdown voltage, the gate driver voltage is limited to 5 V, which requires extra protection circuits for an all-GaN integrated circuit (IC) development.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…A. Chvá la et al demonstrated a monolithic NAND cell that is based on InAlN/GaN MIS-HEMTs with a maximum gate voltage of 3 V, and confirming the validity of the proposed models [20]. As an essential building block for digital circuits, implementing dual-gate E-mode NAND (DG-NAND) by p-GaN HEMTs with a smaller area provides an optimization method [21]. However, as a result of the limitations of p-GaN technology with low gate breakdown voltage, the gate driver voltage is limited to 5 V, which requires extra protection circuits for an all-GaN integrated circuit (IC) development.…”
Section: Introductionmentioning
confidence: 68%
“…Papers [18] and [30] uses a second gate to complete the design of a bidirectional device. Both papers [20] and [21] utilize a dualgate structure for the functional block of the monolithic integrated GaN platform. Verifying the dynamic performance and comparing it with the conventional design is necessary.…”
Section: Table I Comparison For Gan-based Dual-gate Devicementioning
confidence: 99%
“…This section presents the design of the monolithic integrated GaN active rectifier diode in a p-GaN power IC platform. The platform with building blocks is presented in [36]. A first hybrid design was published in [37].…”
Section: Gan Power Ic Designmentioning
confidence: 99%
“…With the advent and ascent of gallium nitride (GaN) power transistors, these have been increasingly used in power stages to achieve primarily higher power density and efficiency [1,2]. In addition, the GaN technology with its lateral transistor structure (known as high electron mobility transistors, HEMTs) enables the monolithic integration of additional functions and circuits on a chip to realize cost-effective GaN power ICs [3][4][5][6] used in power converters with a reduced bill of material (BOM) and associated lower relative climate impact [7].…”
Section: Introductionmentioning
confidence: 99%